Statistical methods for the social & behavioural sciences a model-based approach - Flora, David B. (SAGE Publications, Inc., 2018)
Statistical Methods for the Social and Behavioural Sciences: A Model Based Approach is the essential guide for those looking to extend their understanding of the principles of statistics, and begin using the right statistical modeling method for their own data. It is particularly suited to second or advanced courses in statistical methods across the social and behavioural sciences.